Design and Analysis of DC-DC Converter and Battery Charging Method in EV Dynamic Charging - Razali, Aisya Izzaty; Khalid, Hassan; Mubin, Marizan; Mekhilef, Saad (New Explorations in Electrical Engineering, 2025)
Dynamic Wireless Power Transfer (DWPT) has advanced significantly, yet challenges remain, particularly with output pulsations in Electric Vehicles (EVs) during movement. Unlike Static Wireless Power Transfer (SWPT), which maintains a stable output voltage with high efficiency, DWPT experiences fluctuations due to rapid changes in mutual inductance between the transmitter and receiver coils during energy transmission. This paper addresses this issue by implementing a DC-DC converter and a control method for battery charging on the receiver side of the system. Conventional DC-DC converters were examined based on their performance, and the boost converter was selected for its high efficiency. The research progressed with the design of the boost converter, along with the Constant Current-Constant Voltage (CC-CV) control method, enhanced with a Proportional – Integral (PI) controller for battery charging, chosen for its simplicity. The complete system was modeled and simulated in a Simulink environment, followed by extensive testing under dynamic conditions reflective of real-world applications. The results demonstrate that the proposed system effectively reduces output voltage pulsations, keeping them below 0.1%, which is well within the acceptable range of 2%. Efficiency analysis revealed that the proposed system achieved an efficiency range of 96.6% to 99.5%, outperforming existing solutions in terms of efficiency.